Niche Complementarity and Resistance to Grazing Promote the Invasion Success of Sargassum horneri in North America - Lindsay M. Marks; Daniel C. Reed; Sally J. Holbrook (Diversity, 2020)
Invasive species are a growing threat to conservation in marine ecosystems, yet we lack a predictive understanding of ecological factors that influence the invasiveness of exotic marine species. We used surveys and manipulative experiments to investigate how an exotic seaweed, Sargassum horneri, interacts with native macroalgae and herbivores off the coast of California. We asked whether the invasion (i.e., the process by which an exotic species exhibits rapid population growth and spread in the novel environment) of S. horneri is influenced by three mechanisms known to affect the invasion of exotic plants on land: competition, niche complementarity and herbivory. We found that the removal of S. horneri over 3.5 years from experimental plots had little effect on the biomass or taxonomic richness of the native algal community. Differences between removal treatments were apparent only in spring at the end of the experiment when S. horneri biomass was substantially higher than in previous sampling periods. Surveys across a depth range of 0−30 m revealed inverse patterns in the biomass of S. horneri and native subcanopy-forming macroalgae, with S. horneri peaking at intermediate depths (5−20 m) while the aggregated biomass of native species was greatest at shallow (<5 m) and deeper (>20 m) depths. The biomass of S. horneri and native algae also displayed different seasonal trends, and removal of S. horneri from experimental plots indicated the seasonality of native algae was largely unaffected by fluctuations in S. horneri. Results from grazing assays and surveys showed that native herbivores favor native kelp over Sargassum as a food source, suggesting that reduced palatability may help promote the invasion of S. horneri. The complementary life histories of S. horneri and native algae suggest that competition between them is generally weak, and that niche complementarity and resistance to grazing are more important in promoting the invasion success of S. horneri.